KERAGAMAN MAKROFAUNA TANAH DI BAWAH TEGAKAN TANAMAN KARET (Havea brasiliensis Muell. Arg) DI LAHAN GAMBUT YANG DITUMBUHI DAN TIDAK DITUMBUHI Mucuna bracteata - Aria, Maya; Wawan, Wawan; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Peatlands in Indonesia is one of the natural resources that have the potential for development in the rubber plantation sector. Use of peatlands as a plantation must be managed well to keep it from damage, because peat has great benefits. One way to keep the peatland in order to avoid damage by growing a cover crop Mucuna bracteata.The purpose of this study was to knowing diversity of soil macrofauna and knowing the relationship between the girth of rubber plants that overgrown and not overgrown by Mucuna bracteata. This research has been conducted in areal life plant PT. RAPP Subdistricts Teluk Meranti, District Pelalawan, Riau and analysis soil macrofauna in Soil Laboratory, Faculty of Agriculture, University of Riau. Research was conducted from January until March 2016. Sampling in this research is a purposive sampling of 5% of the 20.4 ha (1.02 ha). The data obtained from the research and calculations such as total individual, family, population density, relative density and diversity of soil macrofauna analyzed descriptively and the data measuring the girth of rubber plants were statistically analyzed. The results showed that life mucuna has a diversity index, total individual, the number of species, population density and relative density greater than without mucuna and died mucuna. Average girth of rubber plants in life mucuna greater than compared to without mucuna and died mucuna.Keywords :Mucuna bracteata, rubber plants, peatlandand soil macrofaunaÂ